Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.resuscitation.2021.01.021
|View full text |Cite
|
Sign up to set email alerts
|

The use of personal protection equipment does not impair the quality of cardiopulmonary resuscitation

Abstract: Aim: Prior studies suggest that the use of personal protective equipment might impair the quality of critical care. We investigated the influence of personal protective equipment on out-of-hospital cardiopulmonary resuscitation. Methods: Randomised controlled non-inferiority triple-crossover study. Forty-eight emergency medical service providers, randomized into teams of two, performed 12 min of basic life support (BLS) on a manikin after climbing 3 flights of stairs. Three scenarios were completed in a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 12 publications
(16 reference statements)
3
42
0
Order By: Relevance
“…These differences are similar to those obtained in a previous study in which they compared the quality of cardiopulmonary resuscitation in two environments with different temperatures, at 25 °C and 37 °C, respectively [ 10 ]. The increase in RPE reflected when performing CPR with PPE is in concordance with other studies, in which perceived fatigue shows higher values when wearing PPE than when not wearing PPE [ 16 , 32 , 33 ]. It would be advisable for healthcare professionals to rest after performing CPR with PPE until their sense of fatigue decreases.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These differences are similar to those obtained in a previous study in which they compared the quality of cardiopulmonary resuscitation in two environments with different temperatures, at 25 °C and 37 °C, respectively [ 10 ]. The increase in RPE reflected when performing CPR with PPE is in concordance with other studies, in which perceived fatigue shows higher values when wearing PPE than when not wearing PPE [ 16 , 32 , 33 ]. It would be advisable for healthcare professionals to rest after performing CPR with PPE until their sense of fatigue decreases.…”
Section: Discussionsupporting
confidence: 91%
“…Due to the decrease in CPR quality evidenced in their systematic review, Sahu et al recommend finding ways to improve CPR without compromising on the safety of the healthcare worker [ 2 ]. Both Kienbacher et al and this study provide evidence for the non-inferiority of resuscitation in longer scenarios [ 33 ]. This study shows a significant decrease in HR during the CPR support phase.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Some studies suggest that physically demanding tasks may be impeded by the mask (Chen et al, 2016 ; Fikenzer et al, 2020 ). Others suggest that while perceived respiratory effort may be increased, vigorous exercise and CPR quality are not affected by masking (Hopkins et al, 2020 ; Kienbacher et al, 2021 ). Mask performance may be reduced by moisture from sweating or heavy breathing.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Since there is evidence for COVID-19 infection transmission during chest compressions, use of personal protective equipment (PPE) has been recommended for health care personnel involved in resuscitating of patients with confirmed or suspected COVID-19 (6)(7)(8). However, studies evaluating the influence of PPE use on the quality of chest compression showed inconsistent results (9)(10)(11)(12)(13)(14). Some simulation-based randomized controlled trials (RCTs) suggested that use of PPE by the CPR providers was associated with compromised quality of chest compression (9,14), while others did not show significant difference regarding the performance of chest compression (10)(11)(12)(13)).…”
Section: Introductionmentioning
confidence: 99%